2022
DOI: 10.3390/geriatrics7050111
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Physical Activity in a Diverse Older Population

Abstract: Physical activity is important for healthy aging, but few older adults achieve the goal of 150 min per week of moderate activity. The purpose of this study was to employ a robust statistical approach in the analysis of the factors related to physical activity in a diverse sample of older adults. A secondary analysis of factors associated with calculated MET-h/week was conducted in a sample of 601 African Americans, Afro-Caribbeans, European Americans, and Hispanic Americans age 59 to 96 living independently in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Apart from established fact that physical health diminishes with aging (10,11), subjective well-being also poses a similar threat to successful aging. However, difficulty to attain good physical health, cognitive and social functioning, as well as achieving economic independence may perhaps reduce the quality of wellbeing in older people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from established fact that physical health diminishes with aging (10,11), subjective well-being also poses a similar threat to successful aging. However, difficulty to attain good physical health, cognitive and social functioning, as well as achieving economic independence may perhaps reduce the quality of wellbeing in older people.…”
Section: Introductionmentioning
confidence: 99%
“…The poor health conditions of the elderly in Africa include body pain, increased rates of HIV and AIDS, nervous disorders, musculoskeletal systems, and ocular diseases (10). For instance, in Southern Africa, it was found that chronic health-related problems common among the older population include HIV/AIDs, arthritis, dementia, and diabetes which are closely linked with obesity, reduced energy and physical activity, and high blood pressure (11)(12)(13). A study conducted in Botswana by the UN (14) revealed that muscle-skeletal pains, hypertension, dermatological problems, blindness, mental health, and cognitive impairment are the most common health challenges facing older people in the region.…”
Section: Introductionmentioning
confidence: 99%
“…For example, social network, depression, and pain can be ameliorated by physical activity,” said senior author Ruth M. Tappen, EdD, RN. (See Tappen et al, 2022. )…”
mentioning
confidence: 99%